LOSSES IN WHEAT CROP AS A FUNCTION OF THE WATER CONTENT OF THE GRAINS AT HARVEST - Galindo, Fernando Shintate; Zocoler, João Luis; Teixeira Filho, Marcelo Carvalho Minhoto; Buzetti, Salatiér; Santini, José Mateus Kondo; Alves, Cleiton José; Ludkiewicz, Mariana Gaioto Ziolkowski (REVISTA DE AGRICULTURA, 2018)
The objective was to study the harvest point for the wheat crop, associated maximum grain yield and productive components with different harvest moisture and losses on natural drying in the field with different water levels in grain. The treatments consisted of the following crop moisture levels (on wet basis) of the grains: 27.9 (point of full physiological maturity), 22.6; 19.9; 18.1; 15; and 12.9%, evaluating the number of spikelets per spike, number of voids grains, number of grains per spike and per spikelet, percentage of lodging, thousand grain mass, number of ears per meter, hectoliter mass, and yield. The largest wheat yield was obtained with the grain harvest at physiological maturity point, decreasing linearly until natural drying to 13% (on a wet basis).